Greening Mainstream Politics: Party Organization, Public Office, and Environmental Action in Majalengka, Indonesia - Valina Sinka; M. Ridha Taufiq Rahman; Astri Afrilia (Universitas Islam Darul Ulum Lamongan, 2026)
This article examines how mainstream political parties in Majalengka respond to environmental degradation and asks whether their initiatives amount to meaningful green politics or remain selective political adaptation. The study focuses on Majalengka because the regency faces visible ecological pressure, including extreme local heat and deficits in green open space, which make environmental governance a pressing political issue rather than a peripheral agenda. Using a qualitative case study design, the article analyzes PDI Perjuangan and Golkar through Katz and Mair’s Three Faces of Party framework, namely party in central office, party in public office, and party on the ground. Data were collected through in-depth interviews, observation, and document review, and were validated through source triangulation. The findings show that PDI Perjuangan demonstrates a thicker environmental profile because leadership discourse, institutional access, and grassroots activities reinforce one another. This is reflected in concrete initiatives such as the planting of 221,272 trees, the development of a 3-hectare people’s garden in Simpeureum with 10 food crop varieties, the formation of women farmers’ groups, and drainage repair at the village level. Golkar also articulates environmental concern through leadership statements and policy advocacy on tree cutting and green open space, yet its response remains more procedural and campaign-oriented than socially embedded. The article argues that neither party can be treated as a fully green political actor. PDIP’s activism still carries a productive and food-oriented logic rather than ecological restoration, while Golkar’s regulatory agenda is constrained by bureaucracy, development priorities, and weak implementation. The study contributes to party politics and environmental governance literature by showing that green politics in Indonesia may emerge within mainstream parties, but its depth depends on whether ecological commitment is translated across party organization, public office, and grassroots practice.